Coffee, culture, and conservation Adaptive reuse application and spatial identity of selected Intramuros cafes - Buenaseda, Darla Mei S.; De Vera, Angel Anne M.; Florendo, Rowena Nicole V.
This study investigated the application of adaptive reuse in the interior design of three selected cafe establishments located in Intramuros, Manila—Paper+Cup, Café Y Ruedas, and Papakape. As heritage spaces encounter the dual pressures of preservation and modernization, adaptive reuse offers a sustainable design solution while reinforcing cultural identity. Despite its growing relevance, limited academic literature explores how this approach shapes spatial identity and user experience in the Philippine context. Addressing this gap, the study analyzed how adaptive reuse strategies are applied in commercial interiors within a historic urban landscape. Using a multiple case study framework and mixed-methods approach, the research involved three purposively chosen cafes in Intramuros that applied adaptive reuse, site assessments, interviews with the café owners, and a simulation activity with six participants selected through snowball sampling. Key regulations such as the National Cultural Heritage Act of 2009 (RA 10066), Hazard Analysis and Critical Control Points (HACCP), the Code on Sanitation of the Philippines (PD 856), and the Implementing Rules and Regulations of the Fire Code (RA 9514) guided the evaluation process. Thematic analysis revealed that, despite varied design directions and structural interventions, all three cafes successfully established a functional, culturally resonant, and emotionally engaging sense of place. Participants responded to both tangible heritage features and subtle expressions of Filipino identity, demonstrating how adaptive reuse can preserve atmosphere while serving modern needs. These findings affirm that adaptive reuse is both a technical and cultural strategy that sustains memory and meaning in evolving urban environments. Future research may expand on this by incorporating insights from design professionals, expanding participant samples, or employing comparative methods to further deepen understanding.